The Role of Halal in MSMEs Products Towards a Global Sharia Economy (Case Study on MSMEs in Kudus) - Widya Alfi Yonita; Agung Slamet Sukardi (Universitas Negeri Semarang, 2025)
This study is a literature review that discusses the role of halal in MSME products as a step towards a global sharia economy. This study aims to analyze and provide an understanding of the role and efforts needed for halal products in MSMEs in Kudus City to achieve an international-scale sharia economy. The approach used is a qualitative descriptive method. The data collected are qualitative and consist of primary and secondary data. Data sources are taken from literature available both online and offline, such as scientific journals, books, articles from trusted sources. The results of the study indicate that the role and efforts made towards halal in MSME products in Kudus City can encourage the realization of a global sharia economy. MSMEs have an important role in supporting equitable and sustainable economic growth by implementing sharia principles such as justice and transparency to build a strong sharia economic ecosystem and provide a positive impact on community welfare.